PERANAN MAJELIS PENDIDIKAN DASAR DAN MENENGAH PIMPINAN DAERAH MUHAMMADIYAH ( PDM ) SIDOARJO DALAM PENINGKATAN STANDAR PENDIDIKAN - Sunariyanto, Budi (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) STIT Muhammadiyah Tempurejo, Ngawi, Jawa Timur, 2021)
Regional Leadership Council Dikdasmen Muhammadiyah (PDM), Sidoarjo in quantity supervises approximately 32 elementary and middle schools. Of the many schools that can be categorized as qualited school (superior), there is no doubt it can be counted on the fingers and in the urban area or housing, From the background above, can be formulated in some problem which will be found the answer through this research, namely : How does the role of PDM Dikdasmen Assembly Sidoarjo period of 2005-2010 on improve education standards Muhammadiyah schools in Sidoarjo, response and hope Muhammadiyah schools associated with the role of PDM Sidoarjo Dikdasmen Assembly and what factors are to be supporting and inhibiting the Assembly Dikdasmen PDM Sidoarjo in improving education standards Muhammadiyah schools in the district. Sidoarjo. This research is qualitative, that is an approach to research that produces descriptive data in the form of written data / oral of people and behaviors that can be observed. The results of this study demonstrate the role of assembly-related increase in the standard of education in schools is still quite minimal, both in the program of activities and intensity of activities undertaken. Responses related to the school board's role in improving educational standards in schools, most provide an assessment is even likely still minimal. While the expectations conveyed by the school big enough for assembly further improve its performance in accordance with the functions and roles, improving education standards by a panel of Sidoarjo Dikdasmen PDM has several contributing factors as well as inhibiting factors. Among the supporting factors (1) assembly Dikdasmen PDM Sidoarjo managed by people who are professionals in the field of education, (2) assembly has a fairly harmonious relationship with the education office in Sidoarjo, (3) the existence of excellent schools that can be utilized by the council to help provide guidance. The inhibiting factors, including (1) personal busyness each assembly, (2) the large number of schools is the responsibility of the assembly and spread throughout the district of Sidoarjo (3) lack of budget funds that are owned by the council.